A Preliminary Study on Induced Spawning of the Catfish Clarias batrachus (Linnaeus) in Malaysia - Cheah, S. H.; Siraj, Siti Shapor; Ang, K. J. (1990)
Ten gravid Clarias batrachus females were administered with a single dose of common carp pituitary homogenate (CPR). Bifore injection, the eggs were light yellow and the diameter rangedfrom 0.94 mm to 1.08 mm. Ovulation occurred approximately 12 hours after the adminstration of CPR. The colour of the eggs turned brown and the diameter rangedfrom o. 99 mm to 1.27 mm. The fertilization rates rangedfrom 10-81%. The eggs hatched after about 30-36 hours of incubation at 26°C to 28°C. The hatching rates ranged from 13-67070.